Hubungan Hygiene Sanitasi Makanan dan Kebiasaan Jajan dengan Kejadian Diare pada Balita Usia 12-59 Bulan di Kelurahan Air Tiris - Angraini, Dela Nofri; Isnaeni, Lira Mufti Azzahri; Kusumawati, Nila (Sulolipu: Media Komunikasi Sivitas Akademika dan Masyarakat, 2025)
The World Health Organization (WHO) states that diarrhea is the third leading cause of death in children aged 1–59 months. Each year, this disease causes the death of approximately 443,832 children under 5 years of age, and 50,851 children aged 5 to 9 years. The purpose of this study was to determine the relationship between food hygiene and sanitation and snacking habits with the incidence of diarrhea in toddlers aged 12–59 months in Air Tiris Village. The study design used a quantitative approach with a cross-sectional design. The population of this study was all mothers who had toddlers in Air Tiris Villag e. The sample in this study amounted to 114 respondents taken using cluster sampling. The results of the study obtained a significant relationship between food hygiene and sanitation with the incidence of diarrhea in toddlers aged 12–59 months in Air Tiris Village, with a p-value of 0.003. There was a significant relationship between snacking habits and the incidence of diarrhea in toddlers aged 12–59 months in Air Tiris Village, with a p-value of 0.016. Parents, especially mothers of toddlers, are expected to pay closer attention to the hygiene and sanitation of the food they provide to their children and to monitor their toddlers' snacking habits.